Designing and implementing a new pulsar timer for the Hartebeesthoek Radio Astronomy Observatory - Youthed, Andrew David (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2008)
This thesis outlines the design and implementation of a single channel, dual polarization pulsar timing instrument for the Hartebeesthoek Radio Astronomy Observatory (HartRAO). The new timer is designed to be an improved, temporary replacement for the existing device which has been in operation for over 20 years. The existing device is no longer reliable and is diÂ±cult to maintain. The new pulsar timer is designed to provide improved functional- ity, higher sampling speed, greater pulse resolution, more Â°exibility and easier maintenance over the existing device. The new device is also designed to keeping changes to the observation system to a minimum until a full de-dispersion timer can be implemented at theobservatory. The design makes use of an 8-bit Reduced Instruction Set Computer (RISC) micro-processor with external Random Access Memory (RAM). The instrument includes an IEEE-488 subsystem for interfacing the pulsar timer to the observation computer system. The microcontroller software is written in assembler code to ensure optimal loop execution speed and deterministic code execution for the system. The design path is discussed and problems encountered during the design process are highlighted. Final testing of the new instrument indicates an improvement in the sam- pling rate of 13.6 times and a significant reduction in 60Hz interference over the existing instrument.
Keywords: Astronomical observatories; Radio astronomy; Pulsars; Astronomical instruments; Reduced instruction set computers; Random access memory